2006
DOI: 10.1007/s11434-006-0524-7
|View full text |Cite
|
Sign up to set email alerts
|

A new descriptor of amino acids based on the three-dimensional vector of atomic interaction field

Abstract: A noval molecular structural expression method, three-dimensional vector of atomic interaction field (3D-VAIF), has been newly developed based on electrostatic and steric interaction between different types of atoms. Feature descriptors of single amino acid, i.e. principal component scores of structural information for amino acids (SSIA), are obtained through calculation of structural information of 20 coded amino acids using principal component analysis (PCA) method, and the strict tests are performed on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 34 publications
0
14
0
1
Order By: Relevance
“…It has been widely used by Hellberg et al [13]. Besides, data set of dipeptides, a typical sample set for QSAR studies [3,5,13,15,17,[28][29][30][31], is often utilized to test effectiveness of diverse kinds of amino acid descriptors. For a set of peptide analogues, the chemical structure can now be quantified by describing each varied (Table 5), it was indicated that the QSAR model on ACE inhibition was stable and generalized.…”
Section: Results and Analysis Qsar Model For Angiotensin Converting Ementioning
confidence: 99%
“…It has been widely used by Hellberg et al [13]. Besides, data set of dipeptides, a typical sample set for QSAR studies [3,5,13,15,17,[28][29][30][31], is often utilized to test effectiveness of diverse kinds of amino acid descriptors. For a set of peptide analogues, the chemical structure can now be quantified by describing each varied (Table 5), it was indicated that the QSAR model on ACE inhibition was stable and generalized.…”
Section: Results and Analysis Qsar Model For Angiotensin Converting Ementioning
confidence: 99%
“…[37][38][39] All three datasets have been utilized previously in a number of QSAR analysis or for the development of novel descriptors for amino acids. Tropsha et al had utilized the bradykinin-potentiating pentapeptides for the development of a novel strategy for rational design of targeted peptide libraries.…”
Section: Datasetsmentioning
confidence: 99%
“…35,37,[39][40][41]44 Tables 8-10 draw a comparison between the eQSAR models and the published literature for the respective three datasets. For the bradykinin-potentiating pentapeptides, the regression coefficient (r 2 ), and crossvalidation coefficient (q 2 ) are comparable with the Z-scales method by Hellberg et al, and the WHIM descriptors-based statistics.…”
Section: Comparative Studies Of Eqsar Model Statistics With Other Pubmentioning
confidence: 99%
“…Through simulating structural characteristics of active site to combine within angiotensin I, ACE inhibitors can arrive at the aim of competitively inhibiting effective bioactivity of ACE. As a classical dataset, 58 dipeptides of ACE inhibitors have ever been used to test validity for new types of amino acids descriptors [2,9,[37][38][39][40][41][42] . The primary sequence and bioactivity, expressed with pIC 50 (see supplymenteny materials Table A5 for electronic version), of this dataset are taken from reference [37] Owing genetic algorithm (GA) being a stochastically searching algorithm, the computational results correspond definite uncertainty.…”
Section: Angiotensin Converting Enzyme Inhibitorsmentioning
confidence: 99%